Studies on Fractal Microstrip Antenna Arrays for Wireless Mimo Applications - Singh, Jaivinder (My University, 2018)
As the world is moving very fast in the perspective of technology, wireless communication plays a vital role in the making a better future. Antennas are the devices by which we can transfer the data wirelessly. There are many types of antennas with different shapes and sizes. Nowadays every modern wireless equipment is implemented with Wi-Fi (Wireless WLAN), Bluetooth and many more such technologies. For the same we need broadband and multi-band antennas to cover the various applications in a same terminal device. In order to have better transmitting and receiving rate broadband antennas are required. In addition, for miniaturising the wireless communication system, the antennas must be small enough to be placed inside the system. The microstrip antennas have various advantages that make them a good candidate for their use in the current wireless communication systems. The main focus nowadays is to increase the speed of the data communication in the antenna with minimum noise, so MIMO antennas came into being. Therefore the research work presented in this thesis concentrates on the study of fractal aperture coupled microstrip antenna arrays that can be used in the MIMO systems. The research work starts with firstly designing a simple aperture coupled square patched antenna with edges sliced which covers a bandwidth of 139.4 MHz from 2.364 GHz to 2.5034 GHz. Then a sierpinski gasket fractal antenna and hexagonal antenna with defected ground structure and aperture coupling is designed which is then converted into 2x2 MIMO antenna and these cover a bandwidth of 1.006 GHz from 5.4832 GHz to 6.4892 GHz for a 2x2 MIMO array. Secondly, a hexagonal antenna with defected ground structure and aperture coupling is designed. This shows dual-band behaviour for frequencies between (5.139-5.274) GHz and (8.71-9.44) GHz for WLAN and X-band applications. It is also converted to an array with two antennas and can be used for a 2x2 MIMO antenna array. The research work is then extended to surface capable of allowing particular range of frequency and rejecting all other unwanted frequencies. An antenna based on FSS is also designed to provide selective band behaviour from the antenna. In this thesis the FSS based antennas focuses on the implementation of a bandstop filter from 8 GHz to 10 GHz and covering a dual band from (3.67-3.75) GHz and (6.44-7.88) GHz. This designed antenna is suitable for IEEE 802.11, C-band, X-band applications. Lastly two fabricated antennas i.e. 2x2 triangular sierpinski gasket fractal antenna and hexagonal antenna with defected ground structure are tested using VNA to validate the results. The tested results and the comparison of tested and simulated results are also shown. A good match between the simulated and tested results allows the antenna to be suitable for desired wireless applications.
Master of Engineering - Wireless Communication
Keywords: MIMO Arrays; Fractal Antennas; Diversity Gain